Auto-acetylation on K289 is not essential for HopZ1a-mediated plant defense suppression - Rufián, José S.; Lucía, Ainhoa; Macho, Alberto P.; Orozco-Navarrete, Begoña; Arroyo-Mateos, Manuel; Bejarano, Eduardo R.; Beuzón, Carmen R.; Ruiz-Albert, Javier (Frontiers in Microbiology, 2015)
The Pseudomonas syringae type III-secreted effector HopZ1a is a member of the HopZ / YopJ superfamily of effectors that triggers immunity in Arabidopsis. We have previously shown that HopZ1a suppresses both local (effector-triggered immunity, ETI) and systemic immunity (systemic acquired resistance, SAR) triggered by the heterologous effector AvrRpt2. HopZ1a has been shown to possess acetyltransferase activity, and this activity is essential to trigger immunity in Arabidopsis. HopZ1a acetyltransferase activity has been reported to require the auto-acetylation of the effector on a specific lysine (K289) residue. In this paper we analyze the relevance of autoacetylation of lysine residue 289 in HopZ1a ability to suppress plant defenses, and on the light of the results obtained, we also revise its relevance for HopZ1a avirulence activity. Our results indicate that, while the HopZ1aK289R mutant is impaired to some degree in its virulence and avirulence activities, is by no means phenotypically equivalent to the catalytically inactive HopZ1aC216A, since it is still able to trigger a defense response that induces detectable macroscopic HR and effectively protects Arabidopsis from infection, reducing growth of P. syringae within the plant. We also present evidence that the HopZ1aK289R mutant still displays virulence activities, partially suppressing both ETI and SAR.